Conduction velocity of the cold spinal pathway in healthy humans. (6th September 2020) - Leone, Caterina; Di Lionardo, Andrea; Diotallevi, Giulia; Mollica, Cristina; Di Pietro, Giuseppe; Di Stefano, Giulia; La Cesa, Silvia; Cruccu, Giorgio; Truini, Andrea
Abstract: Objectives: We aimed to investigate the conduction velocity of the cold spinal pathway in healthy humans. Methods: Using a cold stimulator consisting of micro‐Peltier elements that was able to produce steep cooling ramps up to −300°C/s, we recorded cold‐evoked potentials after stimulation of the dorsal midline at C5, T2, T6 and T10 vertebral levels and calculated the conduction velocity of the cold spinal pathway. In all participants, we used laser stimulation to deliver painful heat (Aδ‐fibres–mediated) and warm (C‐fibres–mediated) stimuli to the same sites in order to compare the conduction velocity of the cold spinal pathway with that of the nociceptive and warm spinal pathways. Results: Cold stimulation evoked large‐amplitude vertex potentials from all stimulation sites. The mean conduction velocity of the cold spinal pathway was 12.0 m/s, which did not differ from that of the nociceptive spinal pathway (10.5 m/s). The mean conduction velocity of the warm spinal pathway was 2.0 m/s. Discussion: This study provides previously unreported findings regarding cold spinal pathway conduction velocity in humans that may be useful in the assessment of spinal cord lesions as well as in intraoperative monitoring during spinal surgery. Significance: This neurophysiological study provides previously unreported findings on cold spinal pathway conduction velocity in healthy humans. Cold‐evoked potentials may represent an alternative to laser‐evoked potential recording, useful to assess spinothalamic tract in patients with spinal cord lesions and monitor patients during spinal surgery.